The (inter)linguistic ecology of education / La (inter)lingva ekologio de la edukado (InKoj. Philosophy & Artificial Languages, New series, 2010)
ABSTRACT The text is a revised version of a public lecture delivered in Parma,Italy, on February 9, 2010. It outlines a definition of linguistic ecology andanalyzes the role of the formal education system in the linguistic ecology ofmodernity. The shift from solid to liquid modernity is shown to have farreachingimplications for schools and for languages that in turn are bound upwith the ecological health of the planet. I argue that interlinguistics can yieldimportant insights into the linguistic ecology of transmodernity, a systemicalternative to the present sociological impasse.RESUMO La teksto estas reviziita versio de publika prelego prezentita en Parma,Italio, la 9an de februaro, 2010. Ĝi skizas difinon de lingva ekologio kaj analizasla rolon de la formala eduksistemo en la lingva ekologio de la moderneco.Montriĝas ke la transiro de solida al likva moderneco kuntrenas profundajnsekvojn por la lernejoj kaj la lingvoj, kaj ke ĉio ĉi kunplektiĝas kun la ekologiasano de la planedo. Mi argumentas, ke la interlingvistiko povas grave kontribuial nia kompreno pri la lingva ekologio de la transmoderneco, konceptitakiel sistema alternativo al la nuna sociologia sakstrato.